Inhibitors of metalloprotease, γ-sectretase, protein kinase C and Rho kinase inhibit wild-type adenoviral replication. - Alice Liu; Cristhian J Ildefonso; Wesley S Bond; Mary Y Hurwitz; Richard L Hurwitz (PLoS ONE, 2020)
Adenoviruses cause upper respiratory infections, conjunctivitis, keratitis, and gastrointestinal illness. These can be fatal in immunocompromised individuals. Adenoviruses have also been engineered into viral vectors to deliver therapeutic genes or induce immunity as vaccine carriers. The success of ocular gene therapy is driven partly by the immunologic and biochemical influences of the intraocular environment. We have shown that versican and hyaluronan modulate adenoviral vector transgene expression through CD44 signaling. Herein we explored the role of these pathways on virus replication and viral protein expression of wild type adenovirus. We report that the addition of vitreous humor (which contains both versican and hyaluronan) increases viral hexon protein levels. Vitreous humor also increased wild type adenovirus DNA replication in vitro. Metalloproteinase and γ-secretase inhibitors, which inhibit CD44 proteolytic activation, blocked adenoviral replication in vitro. Similarly, protein kinase C and RhoA kinase inhibitors, both proteins associated with CD44 mediated pathways, also inhibited wild type adenoviral replication in vitro. Application of metalloproteinase and γ-secretase inhibitors to human conjunctival explants sharply decreased adenoviral vector gene expression. Our results demonstrate that pharmacologic delivery of these inhibitors is easily achievable. The inhibition of these enzymes should be explored as potential therapies of wild type adenoviral infections.